SIGNIFICANCE OF MOTIVATION IN DEVELOPING STUDENTS’ CREATIVE COOPERATION SKILLS (Scientific journal of the Fergana State University, 2024)
The article explains the role of motivation and “subject-subject” relations in the development of creative cooperation skills in students when using “Bit-lesson” technology.